Glycerides isolated from the aerial parts of Malva verticillata cause immunomodulation effects via splenocyte function and NK anti-tumor activity - Ko, Jung-Hwan (Food Sci Biotechnol, 2018)
A preliminary study revealed that a 10 µg/mL n-BuOH fraction of Malva verticillata aerial parts significantly enhanced splenocyte proliferation and induced significant enhancement of natural-killer (NK) cell activity against tumor cells (YAC-1). This study was initiated to identify the principal components that exhibited these activities, and four glycerides were isolated through repeated SiO(2) and ODS column chromatography. Structures of compounds 1–4 were determined to be (2S)-1-O-palmitoyl glyceride, (2S)-1-O-stearoyl glyceride, (2S)-1-O-linolenoyl glyceride, and (2S)-1,2-di-O-linoleoyl glyceride, respectively. Compounds 1–3 showed potential immune-enhancing activity in murine splenocyte and natural-killer (NK) cells at 10 µM. In contrast, compound 4 showed weak activity, indicating the monoacyl glycerides (1–3) are more effective than diacyl glyceride (4). Also, the longer the carbon number of the fatty acid in monoacyl glyceride, the better the activity, and the monoacyl glyceride including an unsaturated fatty acid (3) is more effective than the glycerides including the saturated fatty acids (1–2).